RETRACTED: Achieving Carbon Neutrality – The Role of Heterogeneous Environmental Regulations on Urban Green Innovation - Liu, Baoliu; Wang, Jiaxin; Li, Rita Yi Man; Peng, Lin; Mi, Lili (Frontiers in Ecology and Evolution, 2022)
This article examines the impact of heterogeneous environmental regulations on urban green innovation using panel data from 285 prefecture-level cities in mainland China from 2008 to 2019. From the perspective of green patents, this article utilizes a two-way fixed-effect model and the mediation effect model to examine the mechanism of the impact of heterogeneous environmental regulations on urban green innovation in China. Results show that the urban green innovation development progression in China is relatively slow and can be easily influenced by national policies. More specifically, The relationship between the command-based environmental regulation and urban green innovation presents an inverted non-linear U-shaped model, whereas the relationship between the market-based and voluntary environmental regulation presents a positive U-shaped model. Further investigation of this mechanism concludes that the progression of regional green innovation is primarily accelerated by technological development, effective energy allocation, and industrial structural upgrading. However, the implementation of relevant environmental regulations varies, resulting in various green innovation progression rates. Therefore, in order to achieve the carbon neutrality goal that China proposes, the effectiveness of environmental regulation implementation should be improved, as should the coordinated development of various environmental regulation tools.